If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(9X + 4) = 5(5X + 4) Reorder the terms: 3(4 + 9X) = 5(5X + 4) (4 * 3 + 9X * 3) = 5(5X + 4) (12 + 27X) = 5(5X + 4) Reorder the terms: 12 + 27X = 5(4 + 5X) 12 + 27X = (4 * 5 + 5X * 5) 12 + 27X = (20 + 25X) Solving 12 + 27X = 20 + 25X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-25X' to each side of the equation. 12 + 27X + -25X = 20 + 25X + -25X Combine like terms: 27X + -25X = 2X 12 + 2X = 20 + 25X + -25X Combine like terms: 25X + -25X = 0 12 + 2X = 20 + 0 12 + 2X = 20 Add '-12' to each side of the equation. 12 + -12 + 2X = 20 + -12 Combine like terms: 12 + -12 = 0 0 + 2X = 20 + -12 2X = 20 + -12 Combine like terms: 20 + -12 = 8 2X = 8 Divide each side by '2'. X = 4 Simplifying X = 4
| 5(7X-1)=11(3X+2) | | 100-96=31y-35y | | 6(3X+2)=4(4X+7) | | -14m+8m=6-60 | | 9p+5q=63 | | 0=-9t | | 3(X+0.3)=1-X | | 3t+9t=20-10+26 | | 3x+14x-5=0 | | 7(a+3)=49 | | 3(a-1)=2(a+1) | | 13-13=2w-w | | -97-10x=9x+7 | | 7=7c-7 | | 3x+7=-45+10x | | x-9x=80 | | 4e-9=3 | | 3-0.8X=7-X | | x-w=y | | 2-0.66X=5-X | | -55+7=8n | | 4x+33=11x-30 | | 77-3x=33x+17 | | t+3+8(5+t)= | | X+6=0.5X-2 | | 11-9x=61-44x | | 3-28=5a | | 2x+35=5x+12 | | -114-8x=9x+22 | | 4(2X-7)=0 | | 9+5(t+1)+4t= | | 3x+7=-59-9x |